PELATIHAN PENATALAKSANAAN PROTOKOL KESEHATAN BAGI KADER SEBAGAI UPAYA PENCEGAHAN PENULARAN COVID-19 PADA LANSIA - Utami, P.A.S.; Karin, P.A.E.S.; Wijayanti, N.P.A.D.; Yanti, N.P.E.D. (Buletin Udayana Mengabdi; Vol 22 No 3 (2023): Buletin Udayana MengabdiDO - 10.24843/BUM.2023.v22.i03.p05, 2023)
The elderly are vulnerable to Covid-19, so they need support from cadres as a support system in the community. The aim of this community service is to improve the safety of the elderly to be able to avoid Covid-19 by providing training in the management of health protocols for cadres. Activities carried out include education on Covid-19 prevention protocols, education on support for physical, mental and adequate nutrition, hand washing exercises, and training on making hand sanitizers that are not irritating and safe for elderly skin. The participants involved were 40 elderly cadres in Melinggih Gianyar Village and Babahan Tabanan Village utilizing hybrid learning, namely offline and online training. The result is an increase in the ability of cadres by 52.2% where 100% of cadres have good knowledge after training. Statistical test results obtained with the Wilcoxon test showed p value= 0.000?<0.05 (Z= -5.559) which means that there is an effect of providing training on the ability of cadres to prevent the transmission of Covid-19 in the elderly. Mastery of skills for cadres in implementing health protocols is expected to be able to contribute to preventing the transmission of Covid-19 and reducing morbidity in the elderly so that they are still able to live a quality old age. Keywords: covid-19, education, cadres, elderly, training